OzFoodNet quarterly report, 1 April to 30 June 2013 - OzFoodNet Working Group; Boyle, Cathy (Communicable Diseases Intelligence, 2014)
The Australian Government Department of Health established the OzFoodNet network in 2000 to collaborate nationally to investigate foodborne disease. In each Australian state and territory OzFoodNet epidemiologists investigate outbreaks of enteric infection. OzFoodNet conducts studies on the burden of illness and coordinates national investigations into outbreaks of foodborne disease. This quarterly report documents investigations of outbreaks of gastrointestinal illness and clusters of disease potentially related to food, that occurred in Australia between 1 April and 30 June 2013.